2017
DOI: 10.1007/s00289-017-1903-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of new shellac–hydroxypropylmethylcellulose composite for pharmaceutical applications

Abstract: A new pH-responsive carrier matrix was designed from combination of shellac (Sh), hydroxpropylmethylcellulose (HPMC) and acrylic acid (AA). Characterization of materials was done using various advanced instrumentation techniques. The kinetics of thermal decomposition of materials were studied and compared using Coats-Redfern (CR) and Kissinger-Akahira-Sunose (KAS) mathematical models. The Arrhenius equations for thermal decomposition of shellac and chemically modified shellac (Sh-HPMC-AA) were computed to be k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…HPMC films are strong, resilient, entirely lucid, odor-free, tasteless, and oleophobic. HPMC finds importance in pharmaceuticals, controlled drug delivery, materials for biomedical field [7,8]. PVA is the member of famous polymers of mammoth significance by reason of ease of preparation, distinct, enviable distinctiveness prominently for pharmaceutical and biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…HPMC films are strong, resilient, entirely lucid, odor-free, tasteless, and oleophobic. HPMC finds importance in pharmaceuticals, controlled drug delivery, materials for biomedical field [7,8]. PVA is the member of famous polymers of mammoth significance by reason of ease of preparation, distinct, enviable distinctiveness prominently for pharmaceutical and biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The smooth-surface appearance of the matrix in Figure 3 indicates good miscibility for AAc with HPMC and the formation of a new co-polymer argued by the infrared spectroscopy results in Figure 1 . The new morphological features of the HMPC-AAc network should be supported by the outcome of a combination of electrostatic forces, resulting from the presence of contiguous functional groups such as carboxylates, and hydrogen bonding that occurs between adjacent chain segments [ 36 , 37 ]. Microscopy images are consistent with the discussion of X-ray diffractograms ( Figure 2 ) on the highly amorphous nature of this co-polymer, hence inviting application of the glass-transition theory on the mechanical measurements of the following section.…”
Section: Resultsmentioning
confidence: 99%
“…Drug release from shellac-based matrix tablets is influenced by various factors, such as reaction conditions, ,, additive and drug patterns, , and matrix forms, as shown in Table . Shellac-based tablets with controlled drug release behaviors can be prepared by annealing. , Increasing the annealing temperature and shellac content improves the hardness and disintegration time of shellac-based tablets and converts the drug release kinetics from relaxation-controlled to diffusion-controlled release through the in situ polymerization of shellac during annealing. , Similar to the increase in hardness caused by annealing, matrix tablets annealed at 100 °C showed significantly less erosion after a dissolution test (Figure A), which might contribute to a slower drug release .…”
Section: Shellac-based Delivery Systemsmentioning
confidence: 99%
“…Another study reported a pH-responsive carrier matrix designed by chemical cross-linking shellac, hydroxypropyl methylcellulose (HPMC), and acrylic acid (AA) (shellac-HPMC-AA). It controlled the release of 5-amino salicylic acid by Fickian diffusion …”
Section: Shellac-based Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation